2016
DOI: 10.1093/geronb/gbw040
|View full text |Cite
|
Sign up to set email alerts
|

Is Cancer Protective for Subsequent Alzheimer’s Disease Risk? Evidence From the Utah Population Database

Abstract: Objective: Several studies have suggested that cancer is associated with a reduced risk of the development of Alzheimer's disease (AD). This study seeks to improve our understanding of the association between cancer and the development of AD by showing how mortality selection alters this relationship. Method: A retrospective cohort study was carried out examining 92,425 individuals (47,873 women and 44,552 men) from the Utah Population Database with and without a history of any primary cancer identified by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 50 publications
1
38
0
Order By: Relevance
“…No evidence of a protective effect of cancer vis a vis overall LOD and dementia attributable to AD (AD-LOD) in both non-T2DM and T2DM cohorts was noted. This finding is in line with reports from recent population-based studies, who similarly observed nil significant associations (Hanson HA et al, 2016, Schmidt SA et al, 2017, Freedman DM et al, 2016. Upon examining the cause-specific and sub distribution hazard models, my findings suggest that the inverse association observed between cancer, lung cancer and LOD, especially in the T2DM cohort, is most likely due to mortality selection.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…No evidence of a protective effect of cancer vis a vis overall LOD and dementia attributable to AD (AD-LOD) in both non-T2DM and T2DM cohorts was noted. This finding is in line with reports from recent population-based studies, who similarly observed nil significant associations (Hanson HA et al, 2016, Schmidt SA et al, 2017, Freedman DM et al, 2016. Upon examining the cause-specific and sub distribution hazard models, my findings suggest that the inverse association observed between cancer, lung cancer and LOD, especially in the T2DM cohort, is most likely due to mortality selection.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, a retrospective study, using the UTAH population database, examined several different statistical techniques to explore the association between cancer and AD-LOD in 94,435 individuals (Hanson HA et al, 2016). The authors found that different model specifications can change the direction of the results majorly.…”
Section: Studies On Incidence Of Cancer In Individuals With Lod (Ad)mentioning
confidence: 99%
See 1 more Smart Citation
“…One group recently showed that accounting for competing risks eradicates the inverse association between cancer and AD. 17 However, the decision about whether to account for competing risks depends on the question the analysis is trying to answer. 18 When the goal is to measure the association between two diseases for the purpose of determining a causal relationship, then it is appropriate to ignore the competing risk, as is routinely done when using Cox models in an elderly cohort.…”
Section: 1 Discussionmentioning
confidence: 99%
“…The reduced risk of AD in those diagnosed with cancer may be due to higher mortality rates among cancer patients and survivors, especially for cancers with poor survival rates, such as pancreatic cancer. 10 Many studies are limited by small sample sizes 7 11 12 , short follow-up periods 7 9 12 13 , or gender bias. 9 Other issues include appropriate diagnoses and changing guidelines, the potential negative effects of chemotherapy on cognition, and behavioral and sociodemographic variables related to both AD and cancer.…”
Section: Introductionmentioning
confidence: 99%